Loss of Smad7 Promotes Inflammation in Rheumatoid Arthritis - Zhou, Gengmin; Sun, Xiaolin; Qin, Qingxia; Lv, Jiyang; Cai, Yueming; Wang, Meiying; Mu, Rong; Lan, Hui-yao; Wang, Qing-Wen (Frontiers in Immunology, 2018)
OBJECTIVE—Smad7 is an inhibitory Smad and plays a protective role in many inflammatory diseases. However, the roles of Smad7 in rheumatoid arthritis (RA) remain unexplored, which were investigated in this study. METHODS—The activation of TGFβ/Smad signaling was examined in synovial tissues of patients with RA. The functional roles and mechanisms of Smad7 in RA were determined in a mouse model of collagen-induced arthritis (CIA) in Smad7 wild-type (WT) and knockout (KO) CD-1 mice, a strain resistant to autoimmune arthritis induction. RESULTS— TGF-β/Smad3 signaling was markedly activated in synovial tissues of patients with RA, which was associated with the loss of Smad7, and enhanced Th17 and Th1 immune response. The potential roles of Smad7 in RA were further investigated in a mouse model of CIA in Smad7 WT/KO CD-1 mice. As expected, Smad7-WT CD-1 mice did not develop CIA. Surprisingly, CD-1 mice with Smad7 deficiency developed severe arthritis including severe joint swelling, synovial hyperplasia, cartilage damage, massive infiltration of CD3+ T cells and F4/80+ macrophages, and upregulation of proinflammatory cytokines IL-1β, TNFα, and MCP-1. Further studies revealed that enhanced arthritis in Smad7 KO CD-1 mice was associated with increased Th1, Th2 and, importantly, Th17 over the Treg immune response with overactive TGF-β/Smad3 and proinflammatory IL-6 signaling in the joint tissues. CONCLUSIONS—Smad7 deficiency increases the susceptibility to autoimmune arthritis in CD-1 mice. Enhanced TGF-β/Smad3-IL-6 signaling and Th17 immune response may be a mechanism through which disrupted Smad7 causes autoimmune arthritis in CD-1 mice.